A proteomic analysis of plant programmed cell death. - Swidzinski, J; Leaver, C; Sweetlove, L (2004)
Programmed cell death (PCD) is an active cellular suicide that occurs in animals and plants throughout development and in response to both abiotic and biotic stresses. In contrast to animals, little is known about the molecular machinery that regulates plant PCD. We have previously identified transcriptomic changes associated with heat- and senescence-induced PCD in an Arabidopsis cell suspension culture [Plant J. 30 (2002) 431]. However, since plant PCD is also likely to involve elements that are regulated post-transcriptionally, we have undertaken a proteomic analysis in the Arabidopsis system. We identified 11 proteins that increased in abundance relative to total protein in both treatments despite extensive degradation of other proteins. We argue that some of these proteins are maintained during PCD and may therefore have specific functions in the PCD pathway. The increased abundance of several antioxidant proteins as well as a measured increase in free Fe2+ content of the cells indicates an oxidative stress in this system. Several mitochondrial proteins were identified, confirming the importance of this organelle during PCD. We also identified an extracellular glycoprotein that may function in the transmission of a 'death signal' from cell to cell. Putative roles for the identified proteins are presented.